Mesenchymal Stromal Cells Protect Endothelial Cells from Cytotoxic T Lymphocyte‐Induced Lysis. (September 2016) - Cahill, E. F.; Sax, T.; Hartmann, I.; Haffner, S.; Holler, E.; Holler, B.; Huss, R.; Günther, C.; Parolini, O.; Kolch, W.; Eissner, G.
Abstract: The integrity of the vasculature plays an important role in the success of allogeneic organ and haematopoietic stem cell transplantation. Endothelial cells (EC) have previously been shown to be the target of activated cytotoxic T lymphocytes (CTL) resulting in extensive cell lysis. Mesenchymal stromal cells (MSC) are multipotent cells which can be isolated from multiple sites, each demonstrating immunomodulatory capabilities. They are explored herein for their potential to protect EC from CTL‐targeted lysis. CD8 + T cells isolated from human PBMC were stimulated with mitotically inactive cells of a human microvascular endothelial cell line (CDC/EU.HMEC‐1, further referred to as HMEC) for 7 days. Target HMEC were cultured in the presence or absence of MSC for 24 h before exposure to activated allogeneic CTL for 4 h. EC were then analysed for cytotoxic lysis by flow cytometry. Culture of HMEC with MSC in the efferent immune phase (24 h before the assay) led to a decrease in HMEC lysis. This lysis was determined to be MHC Class I restricted linked and further analysis suggested that MSC contact is important in abrogation of lysis, as protection is reduced where MSC are separated in transwell experiments. The efficacy of multiple sources of MSC was also confirmed, and the collaborative effect of MSC and the endothelium protective drug defibrotide were determined, with defibrotide enhancing the protection provided by MSC. These results support the use of MSC as an adjuvant cellular therapeutic in transplant medicine, alone or in conjunction with EC protective agents such as defibrotide.